FORECASTING OF EFFICIENCY OF THE TITANIUM ALLOYS THERMAL STRENGTHENING - V. N. Fedulov (Литьë и металлургия)
The method of forecasting of the titanium alloys thermal strengthening efficiency, based on the comparison tests of the characteristics c f the variable cross-section slugs is worked out.